Younger next year* : the exercise program - Crowley, Chris; Lodge, Henry S. (Workman Publishing, 2016)
"The exercise book that the one-million-plus readers of the Younger next year series have been waiting for. The exercise book that takes the intimidation out of starting a workout regimen, then serves as a detailed guide for life. The exercise book based on the science that shows how we can turn back our biological clocks by a combination of aerobics and strength fitness. The exercise book that will show every reader, no matter how young or old, how to live with newfound vibrancy, strength, endurance, confidence, and joy"--